2018
DOI: 10.1016/j.midw.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

`It makes sense and it works': Maternity care providers' perspectives on the feasibility of a group antenatal care model (Pregnancy Circles)

Abstract: Pre-registration education inadequately prepared midwives for group care. Addressing sticking points and securing management support for Pregnancy Circles is vital to sustain participation in this model of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…10,30,31,41 Complex health interventions require coordination of multiple types of staff and training, 42 highlighting the deleterious impact of inadequate resources on sustainability. 29,30,43 In this study, group care was integrated within a residency program, enhancing administrative buyin. In contrast, Pekkala et al found that sites with graduate medical education programs reported barriers to administrative buy-in, owing to the need to ensure adequate resident clinical experience; they proposed creative programming to enable residency programs to incorporate group care, as reported here.…”
Section: Discussionmentioning
confidence: 99%
“…10,30,31,41 Complex health interventions require coordination of multiple types of staff and training, 42 highlighting the deleterious impact of inadequate resources on sustainability. 29,30,43 In this study, group care was integrated within a residency program, enhancing administrative buyin. In contrast, Pekkala et al found that sites with graduate medical education programs reported barriers to administrative buy-in, owing to the need to ensure adequate resident clinical experience; they proposed creative programming to enable residency programs to incorporate group care, as reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings demonstrate the challenges of implementation science in maternity care within nations that are less than affluent. To manage sociocultural barriers, it can be helpful to adapt an intervention to a given context [113,140,159,161]-this might Mixed-methods 27 Case study 12 [139][140][141][142][143][144][145][146][147][148][149][150] Pre-post study 8 [151][152][153][154][155][156][157][158] Ethnography 6 [159][160][161][162][163][164] Cohort study 4 [165][166][167][168] Pilot-test 8 [169][170][171][172][173][174][175][176] Longitudinal survey 2 [177,178] Quasi-experimental 1 [179] Randomised controlled trial 2 [180,…”
Section: Theories Models and Framework: Absentmentioning
confidence: 99%
“…This study is part of a NIHR-funded Programme Grant for Applied Research, the REACH Pregnancy Programme (Reference RP-DG-1108-10,049), which aims to improve women's access to, engagement with, and experience of antenatal care. The Programme comprises four main components including this trial and a two-stage feasibility/pilot study preceding it [4,21,23].…”
Section: Why Might Group Antenatal Care Be Beneficial?mentioning
confidence: 99%
“…Better birth experiences have the potential to impact on the wellbeing of women and their children [ 17 – 20 ]. Additionally, recent evidence has shown that midwives trained to deliver group antenatal care report satisfaction with working in this way [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation